2015
DOI: 10.5603/fm.a2018.0037
|View full text |Cite
|
Sign up to set email alerts
|

Celiac trunk and common hepatic artery variations in children: an analysis with CT angiography

Abstract: The prevalence of celiac trunk and hepatic artery variations are high in children as much as in their elders. Awareness of these variations by is important in terms of avoiding iatrogenic injury and in promoting surgical procedure planning for liver transplantation or abdominal tumor surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
(29 reference statements)
0
12
1
4
Order By: Relevance
“…Furthermore, Adachi's and Michel's classifications described in textbooks were recently considered to create a scheme of the most frequent variants of the celiac trunk and anatomy of the hepatic circulation [19,24]. Michel's classification was also used for depiction of CT and CHA variations in children [27]. Favelier et al mentioned that this classification provides the best anatomical approach [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Adachi's and Michel's classifications described in textbooks were recently considered to create a scheme of the most frequent variants of the celiac trunk and anatomy of the hepatic circulation [19,24]. Michel's classification was also used for depiction of CT and CHA variations in children [27]. Favelier et al mentioned that this classification provides the best anatomical approach [28].…”
Section: Discussionmentioning
confidence: 99%
“…(14) Another study, found 90.2 % of population with type I classification and 9.8% with other variations. (15)…”
Section: Image Processingmentioning
confidence: 99%
“…The CT normally originates as the first ventral branch, supplying the foregut (i.e. the stomach, spleen, pancreas, liver, and part of the duodenum) [3,4,7,9,10,12,14,16,18,[24][25][26]33,34,[39][40][41][42]. Venous drainage of the foregut is principally through the portal vein (PV).…”
Section: Celiac Trunk Variationsmentioning
confidence: 99%
“…The CT, also known as the coelic artery, coelic axis or truncus coeliakus, usually arises just below the aortic hiatus at the level of the intervertebral disc between the T12 and L1 vertebrae. The CT is normally 1.5 to 2.3 cm long, and its trunk traverses horizontally forward, trifurcating into the LGA, CHA, and SA (55-100% of the population) [1,3,4,[6][7][8][9][10]12,14,16,18,[23][24][25][26]28,29,33,34,[39][40][41][42][43][44]. This trifurcation was first described by Haller in 1756 as tripus Halleri [7,8,18,21,22,24,28,30,35,45,46].…”
Section: Celiac Trunk Variationsmentioning
confidence: 99%